Human Polyomavirus 7–Associated Pruritic Rash and Viremia in Transplant Recipients. (17th September 2014) - Ho, Jonhan; Jedrych, Jaroslaw J.; Feng, Huichen; Natalie, August A.; Grandinetti, Lisa; Mirvish, Ezra; Crespo, Maria M.; Yadav, Dhiraj; Fasanella, Kenneth E.; Proksell, Siobhan; Kuan, Shih-Fan; Pastrana, Diana V.; et al.
Abstract: Human polyomavirus 7 (HPyV7) is one of 11 HPyVs recently discovered through genomic sequencing technologies. Two lung transplant recipients receiving immunosuppressive therapy developed pruritic, brown plaques on the trunk and extremities showing a distinctive epidermal hyperplasia with virus-laden keratinocytes containing densely packed 36–45-nm icosahedral capsids. Rolling circle amplification and gradient centrifugation testing were positive for encapsidated HPyV7 DNA in skin and peripheral blood specimens from both patients, and HPyV7 early and capsid proteins were abundantly expressed in affected tissues. We describe for the first time that HPyV7 is associated with novel pathogenicity in some immunosuppressed individuals.